Mortality in immatures of the floodwater mosquito Ochlerotatus albifasciatus (Diptera: Culicidae) and effects of parasitism by Strelkovimermis spiculatus (Nematoda: Mermithidae) in Buenos Aires Province, Argentina - Campos, Raul Ernesto (2003)
Life tables were constructed for six cohorts of immature stages of the floodwater mosquito Ochlerotatus albifasciatus (Macquart) in a park in Buenos Aires, highlighting the mortality attributable to the parasitic nematode, Strelkovimermis spiculatus Poinar & Camino. Two cohorts were selected to compare parasite incidence in all mosquito stages when low and high parasitism occurred. Development time of Oc. albifasciatus from first instar to adult was 7.7-10 days in the spring, 6 days in the summer, and 10.9-21.9 days in the fall. Survival was estimated as 0-1.4% in the spring, 2% in the summer and 0.2-4.4% in the fall. The highest K value (Killing power) occurred during a fall cohort when prevalence of the parasite was 86.9%, and the lowest in a spring cohort. Parasitism occurred during all seasons, but S. spiculatus persisted to adult only in the summer and fall, when adult mosquitoes developed from parasitized third and fourth instars larvae. The abundance of S. spiculatus differed between old and young larvae only when parasite prevalence was the highest. Although pupae and adults of Oc. albifasciatus were parasitized, no pupal mortality attributable to parasitism was recorded. The proportion of parasitized adults ranged from 14.2% and 5.7% in the two cohorts compared. Pupal wet weight and adult wing lengths did not differ between parasitized and unparasitized individuals.